Multicentre descriptive cross-sectional study of Japanese home visit patients: reasons for encounter, health problems and multimorbidity. (5th October 2019) - Kaneko, Makoto; Van Boven, Kees; Takayanagi, Hiroshi; Kusaba, Tesshu; Yamada, Takashi; Matsushima, Masato
Abstract: Background: GP in Japan are encouraged to conduct home visits for older adults. However, most previous studies on home visits were based on secondary analyses of billing data that did not include reasons for the encounter. Objectives: This study aimed to describe home visit care by GP in Japan, including reasons for encounter, health problems, episodes of care, comprehensiveness and multimorbidity. Methods: This multicentre descriptive cross-sectional study used the International Classification of Primary Care, second edition, and was conducted in Japan from 1 October 2016 to 31 March 2017. Participants were patients who received home visits from 10 enrolled GPs working in urban and rural areas across Japan. The main outcome measures were reasons for encounter, health problems and multimorbidity. Results: Of 253 potential patient participants, 250 were included in this analysis; 92.4% were aged 65 years and older. We registered 1, 278 regular home visits and 110 emergency home visits. The top three reasons for encounters home visits were associated with cardiovascular and gastrointestinal disorders: prescriptions for cardiovascular diseases ( n = 796), medical examination/health evaluation for cardiovascular diseases ( n = 758) and prescriptions for gastrointestinal problems ( n = 554). About 50% of patients had multimorbidity. Cardiovascular, endocrine and neuropsychological diseases were the most frequent problems in patients with multimorbidity. Conclusions: The main reasons for encounter were prescriptions for chronic conditions. Emergency visits accounted for 8% of all visits. Around half of the patients had multimorbidity. This information may help GPs and policy makers to better assess home visit patients' needs.